Unequal Burden of Disease, Unequal Participation in Clinical Trials: Solutions from African American and Latino Community Members - Ford, Marvella E. (Oxford University Press, 2013)
African Americans and Latinos are underrepresented in clinical trials. The purpose of this study was to elicit solutions to participation barriers from African Americans and Latinos. Fifty-seven adults (32 African Americans, 25 Latinos) ages 50 years and older participated. The Institute of Medicine's Unequal Treatment conceptual framework was used. Six racially/ethnically homogenous focus groups were conducted at five sites in three counties. Themes within groups and cross-cutting themes were identified. The NVIVO program was used for data classification. The data were reviewed for final coding and consensus. Shared solutions included addressing costs, recruiting in community contexts, conducting community and individualized patient education, and sharing patient safety information. Participants were unanimously in favor of clinical trials navigation recruitment interventions. Solutions specific to African Americans included diversifying research teams, recognizing past research abuses, and increasing community trust. Solutions specific to Latinos included providing low-literacy materials, providing Spanish-speaking clinicians and advocates, and clarifying that immigration status would neither be documented nor prevent participation. Solutions from African Americans and Latinos reflect their cultural backgrounds and historical experiences. The results suggest the importance of developing a tailored, barriers-focused navigation intervention to improve participation among diverse racial and ethnic populations.